The influence of education on increasing mothers' knowledge about acupressure for treating children with coughs and colds on increasing - Engelina Choiru Fitroti; Sandi Alfa Wiga Arsa; Anita Rahmawati (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
A mother's knowledge of caring for young children is influenced by information. Information can provide direct knowledge gains that contribute to behavioral change, including the use of complementary therapies such as acupressure. Mothers with young children at the primary service integration cadres “Cut Muti”, in Bendogerit Village, Blitar City, are a strategic group for empowerment because they play a central role in daily childcare. This study uses a one-group pretest-posttest pre-experimental design. The population consisted of 40 mothers of children under five who were registered at the the primary service integration cadres “Cut Muti”, using a total sampling technique. Data was collected using a questionnaire that measured mothers' knowledge of acupressure for managing coughs and colds in toddlers. The intervention consisted of health education thru lectures and counseling supported by leaflets, delivered individually, and conducted in a single 25-minute session. The data was analyzed using the Wilcoxon test. Statistical analysis shows a significant increase in mothers' knowledge after the intervention, with a p-value of 0.000 (p<0.05). This finding indicates a significant difference in knowledge levels before and after health education about acupressure therapy. Health education about acupressure effectively improves mothers' knowledge and is expected to support independent and correct home management of coughs and colds in toddlers. Future community service initiatives are recommended to expand participant coverage and strengthen community-based empowerment programs to sustainably reduce respiratory complaints in children under five in Indonesia.